2020
DOI: 10.1212/wnl.0000000000010003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of neuroinflammation relate to neuropathic pain after spinal cord injury

Abstract: Objective:To determine whether cervical cord levels of metabolites are associated with pain sensation after spinal cord injury (SCI), we performed magnetic resonance spectroscopy in SCI patients with and without neuropathic pain (NP).Methods:Cervical cord single-voxel spectroscopic data of 24 SCI patients (14 with NP, 10 pain-free) and 21 healthy controls were acquired at C2/3 to investigate metabolite ratios associated with neuroinflammation (choline-containing compounds to myo-inositol (tCho/mI)) and neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Spinal cord injury (SCI) not only causes motor dysfunction but also causes neuropathic pain (NP) that is resistant to medical treatment and severely affects the quality of life of patients (Behroozi et al, 2021; Pfyffer et al, 2020; G. Zhang & Yang, 2017). The prevalence of NP after SCI is reported to be 53% to 80% (Brown et al, 2021; Burke et al, 2017; Gruener et al, 2020; Hunt et al, 2021; Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) not only causes motor dysfunction but also causes neuropathic pain (NP) that is resistant to medical treatment and severely affects the quality of life of patients (Behroozi et al, 2021; Pfyffer et al, 2020; G. Zhang & Yang, 2017). The prevalence of NP after SCI is reported to be 53% to 80% (Brown et al, 2021; Burke et al, 2017; Gruener et al, 2020; Hunt et al, 2021; Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) not only causes motor dysfunction but also causes neuropathic pain (NP) that is resistant to medical treatment and severely affects the quality of life of patients (Behroozi et al, 2021;Pfyffer et al, 2020;G. Zhang & Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study investigating pain in mice with pain disorders has shown that TENS relieves nociceptive hyperalgesia and maintains spinal opioid receptors by inhibiting mitogen-activated protein kinase and proinflammatory cytokine expression to activate PKC-γ and P-CREB [ 33 ]. Moreover, Pfyffer et al [ 34 ] have revealed that TENS can excite crude fibers and activate glial cells to release inhibitory neurotransmitters. Thus, the injury sensory signals generated from the same segment of fine fibers on the spinal dorsal horn of the projected neuron’s excitatory action, are inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The application of metabolomics in pain research is still at an early stage [ 67 ]. Notwithstanding this issue, the metabolomics of the CSF in pain patients revealed that neuropathic pain alters sphingomyelin–ceramide metabolism, nervous tissue damage (alanine, taurine) and inflammatory processes (choline) [ 67 , 68 , 69 ]. Choline, which was found to be elevated in IVDH dogs in our study, is a metabolite related to glial activity, and its elevation was found to be linked with worse pain interference [ 69 ].…”
Section: Discussionmentioning
confidence: 99%